The role of multicomponent surface diffusion in growth and doping of silicon nanowires - Efremov, A.; Klimovskaya, A.; Hourlier, D. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2007)
The metal-catalyzed chemical vapor deposition on silicon substrates remains one of the most promising technologies for growing the silicon nanowires up to now. The process involves a wide variety of elementary events (adsorption, desorption, and multicomponent atomic transport with strongly different local mobility, etc.) that take place on the same surface sites and proceed on isolated nano-scaled part of the surface belonging to different individual catalyst particle. In this work, the competition for unoccupied sites during atomic transport under growth doping and percolation-related phenomena on confined parts of surface was treated by the Monte-Carlo simulations. Atomistic simulations were compared with numerical kinetic modeling. Arising nonlinear effects that finally lead to specific modes of the nanoobject growth, shaping, and doping were analyzed. By combining different kinds of simulations and experimental results, the proposed strategy provides a better control at atomic scale of nanowire growth. Both atomistic and kinetic considerations supplementing each other reveal the importance of surface transport and the role of surface immobile contaminations in the nanowire growth.